PENGARUH FINANCIAL LITERACY, FINANCIAL ATTITUDE, GAYA HIDUP, DAN PENDAPATAN ORANG TUA TERHADAP PERILAKU KONSUMTIF MAHASISWA S1 AKUNTANSI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Leonica, Arswarani; Trihastuti , Adiati (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the effect of financial literacy, financial attitudes, lifestyle, and income on the consumer behavior of Accounting students at the University of August 17, 1945 Surabaya. This study uses a quantitative approach with multiple linear regression analysis methods, using IBM Statistics as a measuring instrument. The sample size was 104 respondents, namely 7th semester accounting students at the University of August 17, 1945 Surabaya. The results of this study: 1) Financial Literacy has a significant effect on the consumer behavior of students at the University of August 17, 1945 Surabaya, 2) Financial Attitude does not have a significant effect on the consumer behavior of students at the University of August 17, 1945 Surabaya, 3) Lifestyle has a significant effect on the consumer behavior of students at the University of August 17, 1945 Surabaya, 4) Parental Income has a significant effect on the consumer behavior of students at the University of August 17, 1945 Surabaya.